2017
DOI: 10.29252/ijrm.15.6.357
|View full text |Cite
|
Sign up to set email alerts
|

Genital infections and reproductive complications associated with Trichomonas vaginalis, Neisseria gonorrhoeae, and Streptococcus agalactiae in women of Qom, central Iran

Abstract: Background: Trichomonas vaginalis (T.vaginalis) and Neisseria gonorrhoeae (N.gonorrhoeae) are two most common non-viral sexually transmitted infections in the world. No data are available regarding the epidemiology of genital infections in women of Qom, central Iran. Objective:Epidemiological investigation of sexually transmitted infections in genital specimens of women referred to the referral gynecology hospital in Qom, central Iran.Materials and Methods:Genital swab specimens were collected from women volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 27 publications
0
22
1
Order By: Relevance
“…In this study the frequency of T. vaginalis infection was 32.7% in the studied population. This is higher than our previous report on the general population of the same region [23]. One explanation might be that this study included women with genital complaints.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…In this study the frequency of T. vaginalis infection was 32.7% in the studied population. This is higher than our previous report on the general population of the same region [23]. One explanation might be that this study included women with genital complaints.…”
Section: Discussioncontrasting
confidence: 66%
“…The conditions for N. gonorrhoeae PCR were as follows: initial denaturation of 94°C for 4 minutes, then 30 cycles of 94ºC for 60 seconds, 53.8ºC for 45 seconds, 72°C for 45 seconds, followed by final extension of 72ºC for 10 minutes. Positive results were further confirmed by real-time PCR assay targeting the porA pseudogene as previously described [23]. Sequences of primer pair NIS.F and NIS.R were shown in Table 1 (CinnaGene, Tehran, Iran).…”
Section: Detection Of N Gonorrhoeae Infectionmentioning
confidence: 86%
See 2 more Smart Citations
“…Clinical manifestations of the disease in women possibly contain vulvovaginal irritation, lower abdominal pain, dyspareunia, dysuria, malodorous vaginal discharge [2,14], although the infection is usually asymptomatic in men or in a few cases with the clinical manifestations of dysuria, irritation, urethral discharge [15,16]. In addition, pregnant women infected with T. vaginalis could cause decrease of birth weights, premature rupture of fetal membrane, premature delivery, abortion [17]. Recent studies have shown that T. vaginalis infection is also related to cervical cancer in women [18], prostate cancer in men and infertility [18,19].…”
Section: Introductionmentioning
confidence: 99%